The assembly of ant-farmed gardens: mutualism specialization following host broadening. Issue 1850 (15th March 2017) - Chomicki, Guillaume; Janda, Milan; Renner, Susanne S.
Abstract : Ant-gardens (AGs) are ant/plant mutualisms in which ants farm epiphytes in return for nest space and food rewards. They occur in the Neotropics and Australasia, but not in Africa, and their evolutionary assembly remains unclear. We here use phylogenetic frameworks for important AG lineages in Australasia, namely the ant genus Philidris and domatium-bearing ferns ( Lecanopteris ) and flowering plants in the Apocynaceae ( Hoya and Dischidia ) and Rubiaceae ( Myrmecodia, Hydnophytum, Anthorrhiza, Myrmephytum and Squamellaria ). Our analyses revealed that in these clades, diaspore dispersal by ants evolved at least 13 times, five times in the Late Miocene and Pliocene in Australasia and seven times during the Pliocene in Southeast Asia, after Philidris ants had arrived there, with subsequent dispersal between these two areas. A uniquely specialized AG system evolved in Fiji at the onset of the Quaternary. The farming in the same AG of epiphytes that do not offer nest spaces suggests that a broadening of the ants' plant host spectrum drove the evolution of additional domatium-bearing AG-epiphytes by selecting on pre-adapted morphological traits. Consistent with this, we found a statistical correlation between the evolution of diaspore dispersal by ants and domatia in all three lineages. Our study highlights how host broadening by a symbiont has led to new farming mutualisms.